Determinants of the Internationalization of Family Firms – A Structural Equation Modeling Analysis1 - Nelly Daszkiewicz; Magdalena Olczyk (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
Currently, international behaviors of family businesses (FBs) attract a growing interest of researchers. In an increasingly competitive environment, numerous FBs are forced to expand into foreign markets in search for ways to survive or grow. The article is both theoretical and empirical. In the theoretical part it presents theoretical concepts of FBs internationalization, especially determinants for their going international. In empirical part, the study focuses on two particular internationalization determinants: the attitude of family firm towards internationalization and some aspects of the business environment. Methodology used in this study is unique. Authors use a structural equation modeling (SEM) to explore how strong is a causal effect of the attitude to internationalization and of the business environment to internationalize a firm. The results of the survey are presented on the sample of 216 firms including 88 FBs (were investigated with the use of a survey questionnaire).